PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA PUSAT BIAYA PADA PT BANK RAKYAT INDONESIA UNIT AMPERA MERAUKE (STUDI KASUS PADA PT BANK RAKYAT INDONESIA MERAUKE UNIT AMPERA PERIODE 2017) - Mario Yorgen Aprian; Paulus Peka Hayon (Musamus Accounting Journal, 2018)
This research aims to know the performance level of cost center and responsibility at PT Bank Rakyat Indonesia Ampera Units In Merauke. This research is qualitative research. The data used are the data subjects and documentaries. Research on location of PT. Bank Raktyat Indonesia Ampera Units in Merauke. The results of this research show that the accountability of accounting applied in PT Bank Rakyat Indonesia Unit Ampera Merauke, already applied with good can be seen from the realization does not exceed the amount of the budget which in the set and delegation pertaanggungjawaban given and the process of accountability that are controlled by Pt Bank Rakyat Indonesia Ampera Units In Merauke. Keywords: Accounting accountability, performance assessment and cost center